Actividad de las fosfatasas ácidas y alcalinas (extracelulares e intracelulares) en hongos de la rizosfera de Arachis hypogaea (Papiloneaceae) - Gómez-Guiñán, Y. (Revista de Biología Tropical, 2004)
The potential role of the fungi, isolated from the peanut rhizosphere, in the production of extracellular and intracellular acid and alkaline phosphatase, was evaluated in vitro. Acid and alkaline extracellular phosphatases showed the highest activities, and the Penicillium species were the most efficient in their production. The correlation analysis showed that extracellular acid and intracellular acid phosphatase produced by Aspergillus niger, A. terreus, Penicillium sp. y P. brevicompactum were negatively correlated; while the extracellular and intracellular phosphatase activities, were positively correlated. The extracellular acid phosphatase activities produced in vitro by majority of fungi assayed, were not correlated with the acid phosphatase activity present in the peanut soil rhizosphere. Nevertheless, the extracellular alkaline phosphatase activities produced in vitro, were negatively correlated with the extracellular alkaline phosphatase activities present in the rhizosphere. The ability of phosphatase production by fungi isolated from peanut rhizosphere suggests they have great potential to contribute to the P mineralization in this zone.